The impact of corporate governance, internal control and corporate reputation on employee engagement: a moderating role of leadership style - Poppy Sofia Koeswayo; Haryanto Haryanto; Sofik Handoyo (Cogent Business & Management, 2024)
This study investigates the interplay between Corporate Governance, Internal Control, Corporate Reputation, and Employee Engagement, focusing on the moderating role of different leadership styles. Empirical findings indicate that Corporate Governance, Internal Control, and Corporate Reputation are positively and significantly associated with Employee Engagement. The study further delves into the nuances of leadership styles, democratic, bureaucratic, laissez-faire, and authoritarian, and their distinct moderating effects on these relationships. Democratic leadership was found to enhance the linkage between Corporate Governance, Internal Control, Corporate Reputation, and Employee Engagement. In contrast, the bureaucratic and laissez-faire styles primarily moderated the effects of Internal Control and Corporate Reputation on Employee Engagement. Additionally, authoritarian leadership strongly moderates the relationship between Corporate Governance, Internal Control, and Employee Engagement. These findings suggest that leadership style is crucial in determining the effectiveness of corporate governance mechanisms, internal controls, and reputation management in promoting employee engagement. The study contributes to the broader discourse on organizational behavior and human resource management, offering insights for practitioners and scholars interested in optimizing employee engagement through strategic leadership and organizational practices.This research explores the relationship between Corporate Governance, Internal Control, Corporate Reputation, and Employee Engagement, highlighting the significant role of leadership styles in moderating these dynamics. Findings indicate that democratic leadership amplifies the positive effects of corporate governance, internal controls, and corporate reputation on employee engagement, while bureaucratic and laissez-faire styles show varying impacts on internal controls and reputation. Authoritarian leadership distinctly influences corporate governance and internal control relationships with employee engagement. This study is pivotal for business and management practitioners, offering insights into optimizing employee engagement through strategic leadership and organizational practices.
Keywords: M12; G34; L25; M14; 650; Authoritarian; bureaucratic; democratic; laissez-faire; leadership styles; employee engagement